The Implementation of “Game Based Learning Method” to Improve the Students Speaking Ability Among Seventh Grade Students of MTs. Darul Wustha Jerowaru - Sulhairi (Saniya Institute, 2024)
This research examines the use of game-based learning methods to enhance students' speaking abilities at MTs. Darul Wustha Jerowaru in the year 2024. This study employs Classroom Action Research (CAR) as its research methodology. The statistics in this research were derived from the mean value of student performance and the percentage of grades. The participants in this research were seventh-grade students from MTs. Darul Wustha Jerowaru included 17 individuals. This study was performed in two phases. The tools used in this study included tests, questionnaires, and observation sheets. The mean score of students' speaking proficiency in the first cycle was 69, with 60% of students exhibiting inadequate speaking abilities; hence, the researcher proceeded to a second cycle. The findings indicated that the mean score of students' speaking proficiency was 76, with 81.25% of students meeting the Minimum Completion Criteria (KKM). This indicates that the use of game-based learning methods may enhance students' speaking proficiency.